2010
DOI: 10.1111/j.1469-8749.2009.03604.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of functional progressive resistance exercise strength training on muscle strength and mobility in children with cerebral palsy: a randomized controlled trial

Abstract: AIM To evaluate the effectiveness of functional progressive resistance exercise (PRE) strength training on muscle strength and mobility in children with cerebral palsy (CP).METHOD Fifty-one children with spastic uni-and bilateral CP; (29 males, 22 females; mean age 10y 5mo, SD 1y 10mo, range 6y 0mo-13y 10mo; Gross Motor Function Classification System levels I-III) were randomized to the intervention group (n=26) or the control group (n=25, receiving usual care). The intervention group trained for 12 weeks, thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
140
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(150 citation statements)
references
References 26 publications
7
140
0
3
Order By: Relevance
“…[6][7][8] Previous reports not based on randomized controlled designs may have overestimated the effect that resistance training can have on improving mobility. 1,5 The progressive resistance training programme that led to strength increases in our trial fulfilled key requirements of resistance training including training intensity, frequency, and duration 10,22 and was effective in its intended purpose of increasing muscle strength.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] Previous reports not based on randomized controlled designs may have overestimated the effect that resistance training can have on improving mobility. 1,5 The progressive resistance training programme that led to strength increases in our trial fulfilled key requirements of resistance training including training intensity, frequency, and duration 10,22 and was effective in its intended purpose of increasing muscle strength.…”
Section: Discussionmentioning
confidence: 99%
“…1,5 Although these studies have provided important preliminary evidence to suggest that progressive resistance training could improve mobility, the lack of randomization reduces confidence in the findings. Recent randomized controlled trials that have addressed this limitation have not identified changes in mobility after progressive resistance training in young children 6,7 or in middle-aged adults with CP. 8 However, in these trials, all participants underwent the same exercise programme regardless of their individual presentation.…”
mentioning
confidence: 99%
“…Given that the effect sizes in this metaanalysis obtained 59/0, we can say that the effect of exercise therapy for CP spastic symptoms in children with spastic cerebral palsy is moderate. Based on the findings of this meta-analysis therapists can choose appropriate treatment to decrease CP symptoms to obtain better and more reliable results [11,21,22]. It is proposed that treatment method of nerve development and sensory-motor integration therapy be included in daily programs of these children from practitioners because of being pioneer in serve and treatment of children [11,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…The target movement must be repeated 120-150 times. The authors suggest 75 % of 8 Repetition Maximum (RM) (Scholtes VA et al, 2010) as loading for strengthening movements.…”
Section: Figure 4: Flow Chart Of Step Iii: Identification and Remediamentioning
confidence: 99%
“…8 RM must be calculated for progressive resistance training (Scholtes VA et al, 2010). This may be done by means of a weighted jacket.…”
Section: Stage 3: Functional Embedding -Strength Training In Functionmentioning
confidence: 99%